2016
DOI: 10.18685/ejbme(7)1_ejbme-15-012
|View full text |Cite
|
Sign up to set email alerts
|

Ownership structure, independent directors and firm performance

Abstract: The paper examined the moderating role of independent directors in the relationship between ownership structure and firm performance. Using a sample of 37 finance companies listed on the main market of Bursa Malaysia from 2007 to 2011, the result indicates a significant positive moderating effect of independent directors in the relationship between director ownership and ROA but a negative relationship based on Tobin's Q. The result means that in a company where directors have controlling shares, having indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…Moreover, the findings indicating that more independent directors can lead to better firm performance support Hypotheses 2. The results agree with previous studies (i.e., Baysinger and Butler 1985;Peng 2004;Luan and Tang 2007;Liu et al 2014;Masulis and Mobbs 2014;Kallamu 2016;Singh et al 2018). Thus, the increase of independent directors on boards of firms indeed improves governance and performance of those firms.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the findings indicating that more independent directors can lead to better firm performance support Hypotheses 2. The results agree with previous studies (i.e., Baysinger and Butler 1985;Peng 2004;Luan and Tang 2007;Liu et al 2014;Masulis and Mobbs 2014;Kallamu 2016;Singh et al 2018). Thus, the increase of independent directors on boards of firms indeed improves governance and performance of those firms.…”
Section: Discussionsupporting
confidence: 92%
“…This structure of maintaining the control power by the group with its vested interest may have hindered the effectiveness of the CG code. This finding may partly support Kallamu (2016) and Chen et al (2015) insisting that the strength of independent directors depends on the ownership structure of the firm.…”
Section: Discussionsupporting
confidence: 61%
“…For this reason, Gebba and Aboelmaged (2016) indicated that a typical board should contain a heterogeneous mix of executive and nonexecutive directors. The revised Malaysian Corporate Governance Code (CGCM, 2007) also provided that all publicly traded companies should have a BOD, which should have a balance between executive and non-executive directors to avoid decisions dominated by one group or by some board members (Kallamu, 2016).…”
Section: Board Independencementioning
confidence: 99%